Organoids from pituitary as a novel research model toward pituitary stem cell exploration. Issue 2 (February 2019) - Cox, Benoit; Laporte, Emma; Vennekens, Annelies; Kobayashi, Hiroto; Nys, Charlotte; Van Zundert, Indra; Uji-i, Hiroshi; Vercauteren Drubbel, Alizée; Beck, Benjamin; Roose, Heleen; Boretto, Matteo; Vankelecom, Hugo
Abstract : The pituitary is the master endocrine gland, harboring stem cells of which the phenotype and role remain poorly characterized. Here, we established organoids from mouse pituitary with the aim to generate a novel research model to study pituitary stem cell biology. The organoids originated from the pituitary cells expressing the stem cell marker SOX2 were long-term expandable, displayed a stemness phenotype during expansive culture and showed specific hormonal differentiation ability, although limited, after subrenal transplantation. Application of the protocol to transgenically injured pituitary harboring an activated stem cell population, resulted in more numerous organoids. Intriguingly, these organoids presented with a cystic morphology, whereas the organoids from undamaged gland were predominantly dense and appeared more limited in expandability. Transcriptomic analysis revealed distinct epithelial phenotypes and showed that cystic organoids more resembled the pituitary phenotype, at least to an immature state, and displayed in vitro differentiation, although yet moderate. Organoid characterization further exposed facets of regulatory pathways of the putative stem cells of the pituitary and advanced new injury-activated markers. Taken together, we established a novel organoid research model revealing new insights into the identity and regulation of the putative pituitary stem cells. This organoid model may eventually lead to an interesting tool to decipher pituitary stem cell biology in both healthy and diseased gland.